PRODUCTIVE WAQF AND THE SUSTAINABLE DEVELOPMENT GOALS: POLICY AND INSTITUTIONAL CHALLENGES IN LOCAL WAQF DEVELOPMENT IN INDONESIA - Hardianti Yusuf; Muh. Ruslan Abdullah (Academic Bright Collaboration, 2026)
This study examines why the transformation of traditional waqf into productive waqf remains limited in Indonesia despite its significant potential and explores its relevance for supporting sustainable development at the local level. This study employed a qualitative case study approach in Palopo City, South Sulawesi, Indonesia. Data were collected through semi-structured interviews with 15 participants, including nazhir, officials from the Ministry of Religious Affairs, mosque administrators, religious leaders, and community representatives. Field observations and document analysis of waqf regulations, institutional reports, and policy documents were also conducted. The findings reveal that most waqf assets in Palopo are still utilized for traditional religious purposes such as mosques, prayer rooms, schools, and cemeteries, while productive utilization remains limited. Major barriers include the absence of specialized waqf institutions, limited managerial capacity among nazhir, weak institutional coordination, and dominant traditional perceptions of waqf within the community. Informal and familial patterns in the appointment of nazhir further constrain professional governance and productive asset management. Nevertheless, emerging initiatives, such as the use of mosque waqf land for micro-enterprise rentals, illustrate the potential of productive waqf to support local economic empowerment and social welfare. Although limited to a single local context, this study offers practical implications for the Indonesian Waqf Board, the Ministry of Religious Affairs, local governments, mosque committees, and nazhir development programs by underscoring the need for stronger coordination and professional capacity in productive waqf management. This study contributes local empirical evidence by highlighting the gap between national waqf policies and local implementation while demonstrating the potential contribution of productive waqf to community-based development aligned with the Sustainable Development Goals (SDGs).